A COMPARATIVE ANALYSIS OF THE TYPES OF ANESTHESIA IN TOTAL HIP ARTHROPLASTY - Muntaha Mohammed Murad; Sirar Qahtan Hameed; Zainab Neammah Ahmed (Scholar Express Journals, 2021)
The research aims to know the techniques used for the changes in Total Hip Arthroplasty, where 100 patients were collected from Iraqi Red Crescent Hospital, Baghdad, Iraq. Where two types of anesthesia were released upon, general, the second technique is Lumbar sacral PB, and the ages range between 30 to 60. Over the past decades, Orc replacement has become a major demand. It has expanded in direct proportion to demographic changes, with affected populations experiencing an increased rate of comorbidity and serious complications. It has been suggested that the choice of anesthesia affects the surgical setting and the perioperative outcome as a whole. Therefore, various anesthesia methods and techniques have been developed to provide hip surgery patients with individualized anesthetic and palliative care. Recent studies on comparative efficacy using population-based data have given us new insight into anesthesia practice and outcomes, demonstrating positive outcomes. After surgery, the rehabilitation process requires time and commitment in the first 4-6 weeks after the operation. Walking aids such as crutches and can follow a program of exercises aimed at helping to recover and then improve the use of the new hip joint.
Keywords: AG; Hip; blood; Postoperative dose.